Het oudst bewaarde planetarium van Nederland: de Sphaera Movens, bijgenaamd Leidsche Sphaera. Geschiedenis en restauraties door de eeuwen heen - Hooijmaijers, Hans; Zuidervaart, Huib (Studium, 2015)
Around 1670 in Rotterdam a planetarium was built, depicting the Copernican configuration of the planets. In 1710 this scientific instrument was presented to Leiden University. After an intense refurbishment, the then called Sphaera incomparabilis was placed in the University library, where it could be admired until the beginning of the nineteenth century. After being housed for more than a century in the building of Leiden University Observatory, the instrument was presented in 1931 to the newly erected Museum for the History of Science and Medicine (the forerunner of the present Museum Boerhaave). In recent years the planetarium was restored. This project has triggered new research into the origin and history of the instrument, the results of which are presented in this paper.